Optimized Tetrazine Derivatives for Rapid Bioorthogonal Decaging in Living Cells. Issue 45 (13th October 2016) - Fan, Xinyuan; Ge, Yun; Lin, Feng; Yang, Yi; Zhang, Gong; Ngai, William Shu Ching; Lin, Zhi; Zheng, Siqi; Wang, Jie; Zhao, Jingyi; Li, Jie; Chen, Peng R.
Abstract: The inverse‐electron‐demand Diels–Alder (iDA) reaction has recently been repurposed as a bioorthogonal decaging reaction by accelerating the elimination process after an initial cycloaddition between trans ‐cyclooctene (TCO) and tetrazine (TZ). Herein, we systematically surveyed 3, 6‐substituted TZ derivatives by using a fluorogenic TCO–coumarin reporter followed by LC‐MS analysis, which revealed that the initial iDA cycloaddition step was greatly accelerated by electron‐withdrawing groups (EWGs) while the subsequent elimination step was strongly suppressed by EWGs. In addition, smaller substituents facilitated the decaging process. These findings promoted us to design and test unsymmetric TZs bearing an EWG group and a small non‐EWG group at the 3‐ and 6‐position, respectively. These TZs showed remarkably enhanced decaging rates, enabling rapid iDA‐mediated protein activation in living cells. Abstract : Rapid decaging : The efficiencies of various tetrazine (TZ) derivatives in triggering a decaging reaction based on an inverse‐electron‐demand Diels–Alder process were systematically surveyed. An unsymmetric tetrazine derivative with one electron‐withdrawing substituent and one small alkyl group gave the highest decaging rate and enabled the rapid recovery of protein activity in living cells.